2000
DOI: 10.1681/asn.v115917
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mortality Risk for Dialysis Patients and Cadaveric First Renal Transplant Recipients in Ontario, Canada

Abstract: Abstract. In population-based studies, renal transplantation has been shown to improve survival compared to dialysis patients awaiting transplantation in the United States. However, dialysis mortality in the United States is higher than in Canada. Whether transplantation offers a survival advantage in regions where dialysis survival is superior to that in the United States is uncertain. This study examines a cohort of 1156 patients who started end-stage renal disease (ESRD) therapy and were wait-listed for cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(37 citation statements)
references
References 19 publications
1
35
0
1
Order By: Relevance
“…Over the last few decades, the role of kidney transplantation for managing ESRD has increased significantly and it can be attributed to the cost-effective nature of the treatment with lowered impact on patients’ quality of life as compared to dialysis [ 33 ]. While mortality rates of transplant patients are lower than those on maintenance dialysis, overall patient survival is still worse as compared to the general population [ 34 ]. In this context, efforts have been directed to improve patients’ survival as well as graft survival in kidney transplantation patients.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few decades, the role of kidney transplantation for managing ESRD has increased significantly and it can be attributed to the cost-effective nature of the treatment with lowered impact on patients’ quality of life as compared to dialysis [ 33 ]. While mortality rates of transplant patients are lower than those on maintenance dialysis, overall patient survival is still worse as compared to the general population [ 34 ]. In this context, efforts have been directed to improve patients’ survival as well as graft survival in kidney transplantation patients.…”
Section: Discussionmentioning
confidence: 99%
“…65 Although 44 studies showed an overall benefit favouring transplantation, 11 of those studies identified stratums in which transplantation offered no statistically significant benefit over remaining on dialysis. No difference was reported in patients with kidney failure caused by glomerulonephritis 25 ; patients aged 65-70 years 28 ; patients with kidney failure caused by hypertension or a hereditary cause 30 ; patients with body mass index ≥41 35 ; patients aged ≥70 years with kidney failure caused by glomerulonephritis 45 ; patients receiving standard criteria donor transplantation compared with those on nocturnal haemodialysis 49 ; patients aged ≥70 years on dialysis between 1990 and 1999 50 ; patients classified as being at low risk by the American Society of Transplantation 52 ; patients with peripheral arterial disease receiving deceased donor allografts 59 ; patients aged ≥70 years 67 ; and patients with chronic obstructive pulmonary disease, aged ≥70 years, or with kidney failure caused by diabetes. 58 No study described an overall lower mortality risk associated with dialysis, with 8% (n=4/48) of studies showing no difference in long term survival between treatment modalities.…”
Section: Systematic Review Of Evidencementioning
confidence: 99%
“…Therefore, many researchers have worked on prediction models for kidney-graft survival, classified into three categories: simulation and operation research, conventional statistics, and data analytic approaches [33]. A known subcategory of conventional statistical studies is the Cox proportional hazards model, a widely used multivariate approach in medical literature to assess survival time, which can be utilized for categorical and numerical types of predictors [34][35][36][37][38]. This model aims to evaluate the effects of several variables/covariates on the rate of a specific event (e.g., graft failure) at a particular point in time.…”
Section: Literature Reviewmentioning
confidence: 99%